Exploring the Relationship between Locational and Household Characteristics and E-Commerce Home Delivery Demand - Cheng Cheng; Takanori Sakai; André Alho; Lynette Cheah; Moshe Ben-Akiva (Logistics)
The rapid growth in online shopping and associated parcel deliveries prompts investigation of the factors that contribute to parcel delivery demand. In this study, we evaluated the influence of locational and household characteristics on e-commerce home delivery demand. While past research has largely focused on the impacts of the adoption of online shopping using individual/household survey data, we made use of data from an e-commerce carrier. A linear regression model was estimated considering factors such as degree of urbanization, transit and shopping accessibility, and household attributes. The results both confirm and contradict prior research findings, highlighting the potential for a non-negligible influence of the local context on demand for parcel deliveries.